2013
DOI: 10.2147/dddt.s50972
|View full text |Cite|
|
Sign up to set email alerts
|

Combined letrozole and clomiphene versus letrozole and clomiphene alone in infertile patients with polycystic ovary syndrome

Abstract: BackgroundPolycystic ovary syndrome (PCOS) is the most common endocrine disorder in women of childbearing age (6.8%–18%), is among the most common causes of infertility due to ovulation factors, and accounts for 55%–70% of infertility cases caused by chronic anovulation. In this study, we used a combination of letrozole and clomiphene in patients resistant to both drugs individually, and studied the effects of this combination in ovulation and pregnancy in resistant PCOS patients.MethodsThe study population in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…In other studies, a combination of letrozole and gonadotropin in OI cycles resulted in more mono-ovulation and a shorter ovulation induction duration [19], in addition to a reduced incidence of multiple gestations [6]. Hajishafiha et al [16] reported five cases of twin foetuses (12%) among patients treated with gonadotropins, whereas others reported no multiple pregnancy cases following this type of treatment [17]. Multiple gestations resulted in higher risk of preterm birth and associated neonatal morbidity and expens [20].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In other studies, a combination of letrozole and gonadotropin in OI cycles resulted in more mono-ovulation and a shorter ovulation induction duration [19], in addition to a reduced incidence of multiple gestations [6]. Hajishafiha et al [16] reported five cases of twin foetuses (12%) among patients treated with gonadotropins, whereas others reported no multiple pregnancy cases following this type of treatment [17]. Multiple gestations resulted in higher risk of preterm birth and associated neonatal morbidity and expens [20].…”
Section: Discussionmentioning
confidence: 97%
“…There are a few published studies on the use of CC plus letrozole. In a study on 100 patients resistant to letrozole (four cycles) and CC (six cycles), Hajishafiha et al [16] reported a follicular development rate of 82.9% (213 of 257 cycles) in patients treated with 5 mg of letrozole plus 100 mg of CC daily for 5 D. In the same study, patients received an FSH injection on d 11 if a dominant follicle was present and received HCG trigger when the follicle was > 18 mm in size, followed by intrauterine insemination 36-38 h later. In another combination study, the patients were classified according to age and BMI and randomized to 2.5 mg of letrozole (n = 35) or combination treatment with 2.5 mg of letrozole and 50 mg of CC (n = 35) daily for 3-7 [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hajishafiha et al conducted a population-based survey on 100 patients of infertility who failed to ovulate alone with clomiphene citrate and letrozole as monotherapy, these patients underwent 257 cycles of a combination of letrozole and clomiphene in which 213 were able to form dominant follicle (82.9%), and 44 were unable to do so (17.1%) [ 15 ]. The mean endometrial thickness on the day of human chorionic gonadotropin administration was 8.17 ±1.3 mm and the pregnancy rate was 42%.…”
Section: Discussionmentioning
confidence: 99%
“…23 using letrozole (5 mg) and CC (100 mg) daily for 5 days with an injection of FSH on day 11 in participants who were shown to be resistant to letrozole and CC. 22 However, the methodology of this study was limited in that it took follicular development instead of a valid measure of ovulation as the outcome measure and was conducted without randomization and in a limited population of women with PCOS resistant to single drug treatment of both CC and letrozole.…”
Section: Discussionmentioning
confidence: 99%